Unsettled Conflicts in the Post-Soviet Space in the Analysis of the Western Research Centers - Konstantine Petrovich Kurylev; Artem Levonovich Ngoyan; Eduardo Cabrera Palacios; Olga Vaycheslavovna Skudina (Vestnik RUDN. International Relations, 2016)
The article considers the ideas of some leading western expert analytical centers about the problems of the conflicts development on the CIS space. The subject of research is the positions of the “think tanks” of the USA, Great Britain, Germany and France. Among a large number of the regional conflicts in the CIS the authors focused attention on the conflicts in the East of Ukraine, in Transnistria and in the Nagorno-Karabakh. Such selection is explained by the acute character and impact of these conflicts on the interests of Russia and the other leading states and the international organizations. The theoretical and methodological background of the article consists of the approaches and methods, which are used by the modern political science for the comprehensive analysis of the architecture and structure of the international relations, the mechanism of formation and functioning of the certain states’ foreign policy. The research has the cross-disciplinary character and is made at the intersection of such disciplines as history, political science, conflictology and the international relations. The authors reveal positions of the western “think tanks” on the genesis, evolution and the potential settlement of the armed conflicts in the CIS region. The article highlights the estimates of the western “think tanks” of the reasons of the “frozen” conflicts on the post-USSR space, of the Russian Federation’s role and the participation of external actors (the EU and the USA) in their settlement. Giving the research of the approaches of the western expert analytical centers, the authors reach a conclusion about a set course of the western political scientists’ estimates. It reflects in assignment of a unilateral responsibility for a conflict inhaling or its unleashing on Russia, or on the party of a conflict, closed to the official Moscow. It is particularly obvious in the Ukrainian crisis: the Western countries consider our state as its main initiator. According to the authors, such a narrow-mindedness is coused not by the incompetence of the experts of the “think tanks”, but by the political course and tasks of the power structures of those countries. The western “think tanks”, especially in the USA, are capable to participate directly or indirectly in the political decision-making process. This points to the fact of the political prejudice of the activity of these “think tanks”.